Conjoint bicondylar Hoffa fracture in an adult - Ul Haq, Rehan (Medknow Publications & Media Pvt Ltd, 2013)
Conjoint bicondylar Hoffa fracture is an extremely rare injury. Only one case has been reported previously in the pediatric age group. We describe this injury in a 17-year-old male who presented following a fall with direct impact on his semiflexed right knee. Plain radiographs were inadequate to define the exact pattern of injury. Computed tomographic (CT) scans demonstrated the coronal fracture involving both the femoral condyles which were joined by a bridge of intact bone. The patient was treated with open reduction and internal fixation using swashbuckler (modified anterior) approach. Union occurred within 3 months and at final followup (at 18 months) the patient had a good clinical outcome. The possible mechanism of injury is discussed.